1985
DOI: 10.1111/j.1365-3024.1985.tb00063.x
|View full text |Cite
|
Sign up to set email alerts
|

ACTH‐dependent modulation of malaria immunity in mice

Abstract: Tetracosactrin, a synthetic adrenocorticotrophic hormone (ACTH) analogue delivered by osmotic minipumps implanted s.c. in mice induced a dose-dependent increase of plasma corticosterone levels. In mice with an established immunity to Plasmodium berghei the increase of the plasma corticosterone level due to tetracosactrin treatment correlated with loss of immunity against this malaria parasite. The observed plasma corticosterone levels associated with loss of malaria immunity were of the same order as those in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Despite the established findings of increased GC levels in patients infected with malaria, their functional role has received no recent attention. Studies in the 1980s concluded that in immunized mice, pregnancy-associated increases in corticosterone levels cause the loss of malarial immunity and more recrudescences 16 18 . An earlier and limited study reported that adrenalectomy reduced survival of NMRI mice after P. berghei K173-infection, though the mechanism was not explored 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the established findings of increased GC levels in patients infected with malaria, their functional role has received no recent attention. Studies in the 1980s concluded that in immunized mice, pregnancy-associated increases in corticosterone levels cause the loss of malarial immunity and more recrudescences 16 18 . An earlier and limited study reported that adrenalectomy reduced survival of NMRI mice after P. berghei K173-infection, though the mechanism was not explored 19 .…”
Section: Introductionmentioning
confidence: 99%